1981
DOI: 10.1172/jci110350
|View full text |Cite
|
Sign up to set email alerts
|

Receptor and postreceptor defects contribute to the insulin resistance in noninsulin-dependent diabetes mellitus.

Abstract: A B S T R A C T We have assessed the mechanisms involved in the pathogenesis of the insulin resistance associated with impaired glucose tolerance and Type II diabetes mellitus by exploring, by means of the euglycemic glucose-clamp technique, the in vivo doseresponse relationship between serum insulin and the overall rate of glucose disposal in 14 control subjects; 8 subjects with impaired glucose tolerance, and 23 subjects with Type II diabetes. Each subject had at least three studies performed on separate day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

29
300
6
7

Year Published

1984
1984
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 632 publications
(342 citation statements)
references
References 41 publications
29
300
6
7
Order By: Relevance
“…However, the results seem to warrant subsequent work to substantiate whether increased insulin degradation by insulin-sensitive tissues in vivo is indeed a common feature of Type 2 diabetes and might be involved in the process of peripheral insulin resistance in such patients. This might be of particular importance in view of the now widely accepted notion of post-receptor defects being the predominant origin of insulin resistance in Type 2 diabetes, and not receptor abnormalities [32][33][34][35][36][37], and that intensive insulin treatment seems to be able to ameliorate considerably post-receptor defects, e.g. in insulin-stimulated glucose disposal [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results seem to warrant subsequent work to substantiate whether increased insulin degradation by insulin-sensitive tissues in vivo is indeed a common feature of Type 2 diabetes and might be involved in the process of peripheral insulin resistance in such patients. This might be of particular importance in view of the now widely accepted notion of post-receptor defects being the predominant origin of insulin resistance in Type 2 diabetes, and not receptor abnormalities [32][33][34][35][36][37], and that intensive insulin treatment seems to be able to ameliorate considerably post-receptor defects, e.g. in insulin-stimulated glucose disposal [35].…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetic patients are of particular interest, in whom peripheral insulin resistance due to a combined receptor and post-receptor defect has been implicated in recent years as one pathogenic factor [32][33][34][35][36][37]. Insulin degrading enzyme activity (IDEA) and insulin binding to red blood cells in relation to circulating free insulin concentrations were determined in various groups of Type 2 diabetic patients, including some on sulphonylureas, after short-term insulin treatment, and with severe insulin resistance, and compared with normal subjects and with Type 1 diabetic patients.…”
mentioning
confidence: 99%
“…Insulin resistance is a primary defect of Syndrome-X. Insulin resistance is one of the common characteristics in individuals with NIDDM (Defronzo et al, 1985;Kolterman et al, 1981). Insulin, by acting on insulin like growth factors, causes an increase in vascular smooth muscle cell growth in vitro (King and Goodman, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…IT is well established that patients with type 2 diabetes mellitus are resistant to insulin-mediated glucose utilization [1][2][3][4][5][6]. While skeletal muscle is believed to be the major site responsible for insulin resistance [4], the contribution of the liver to wholebody insulin resistance is poorly understood.…”
mentioning
confidence: 99%
“…To date, however, hepatic insulin resistance in type 2 diabetes remains controversial; some investigators have found that the insulininduced suppression of hepatic glucose output is impaired [5][6][7][8][9], whereas others have not confirmed these findings [3,10]. In the euglycemic hyperinsulinemic clamp method, skeletal muscle glucose uptake can be assumed to approximate the exogenously infused glucose under a plasma concentration of insulin that allows the complete suppression of hepatic glucose output.…”
mentioning
confidence: 99%